Coping of stress and anxiety in the face of death by COVID-19 in older adults - Razo-González, Angélica María (2021)
Object to understand and identify the process and coping mechanisms of perceived stress and anxiety in the face of death, caused by COVID-19 in a sample of elderly men and women. Methodology prospective study, qualitative approach, with semi-structured interviews. Results analysis from salutogenic approach of the Sense of coherence (comprehensibility, manageability and significance), observing elements that allow to develop well-being, adaptability and growth in stressful situations, identifying coping mechanisms. Conclusions from understandability, they manifest feeling overwhelmed, but not threatened, by the situation, from being informed and taking care of themselves, they seek to prevent risk conditions, generating sensation of acting to preserve health, well-being and life itself. From manageability, they require support and easily locate the available resources, although they do not always use them. From significance, they make use of spiritual and religious resources, highlighting the importance of family and community support.